Brick makers, builders and commissioners as agents in the diffusion of Hellenistic fired bricks: choosing social models to fit archaeological data - Östborn, Per; Gerding, Henrik (Journal of Greek Archaeology, 2016)
The general aim of this study is to reach a better understanding of the mechanisms behind the diffusion of fired bricks in Hellenistic Europe, initiated in the north Aegean in the 4th century BC. This is an example of the diffusion of innovations. To this end, a social diffusion model is used to simulate the available archaeological data pertaining to this process. The starting point in the construction of the model is the assumption that different categories of people contributed differently to the diffusion. One aim is to decide the relative importance of these actor groups. The model makes it possible for the innovation to change and evolve along several branches, so that general similarity networks can be simulated. Such networks were previously used by Östborn and Gerding to track the diffusion by identifying likely causal relationships between brick contexts. The modelling strategy is similar to that used by the cultural geographer Torsten Hägerstrand: A simple model, based on a few fundamental principles, is constructed in order to ‘isolate a few crucial factors which go a long way towards substantially explaining the phenomenon in question.’